2008
DOI: 10.1007/s12098-008-0063-0
|View full text |Cite
|
Sign up to set email alerts
|

Rosai-dorfman disease

Abstract: We describe two cases of Rosai-Dorfman disease. One of them had commonly described cervical adenopathy and the second with the very rare bilateral orbital involvement. Both our cases required treatment with steroids because of the danger of pressure symptoms and disfigurement and multiple episodes of high fever in one of them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…33 cases) Systemic symptoms Fever Anemia Fatigue None Not mentioned # of cases 3 5 1 10 9 Ref. [ 25 , 29 , 30 ] [ 3 , 24 , 27 , 29 , 31 ] [ 32 ] [ 17 , 20 , 24 , 28 , 30 , 32 35 ] [ 6 , 17 , 23 , 24 , 26 , 36 38 ] Lesion location Lymph nodes Bone Brain Other # of cases 18 8 5 6 Ref. [ 17 , 22 , 25 , 27 36 , 39 , 40 ] [ 6 , 22 , 24 , 34 , 37 , 40 ] [ 20 , 24 , 26 , 38 , 39 ] [ …”
Section: Discussionmentioning
confidence: 99%
“…33 cases) Systemic symptoms Fever Anemia Fatigue None Not mentioned # of cases 3 5 1 10 9 Ref. [ 25 , 29 , 30 ] [ 3 , 24 , 27 , 29 , 31 ] [ 32 ] [ 17 , 20 , 24 , 28 , 30 , 32 35 ] [ 6 , 17 , 23 , 24 , 26 , 36 38 ] Lesion location Lymph nodes Bone Brain Other # of cases 18 8 5 6 Ref. [ 17 , 22 , 25 , 27 36 , 39 , 40 ] [ 6 , 22 , 24 , 34 , 37 , 40 ] [ 20 , 24 , 26 , 38 , 39 ] [ …”
Section: Discussionmentioning
confidence: 99%
“…Role of radiotherapy and chemotherapy is on trial in case of extensive lesions 9. Although the etiology of RDD is unknown, the leading hypothesis is that it is of infectious origin 110. It has been suggested that RDD may be linked to Parvovirus infection, as Parvovirus B19 capsid proteins have been isolated in some cases 10…”
Section: Discussionmentioning
confidence: 99%
“…The extranodal involvement occurs in 25% of cases 1. Osseous involvement as the only manifestation is unusual 2.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the number of reports showing the usefulness of oral steroid for the treatment of RDD has been increasing. However, the steroid doses reported for RDD have been 1–2 mg/kg per day of prednisolone, 2–4 70 mg/day of prednisolone, 5 60 mg/kg of prednisolone (oral pulse therapy), 6 8–20 mg/day of dexamethasone, 7,8 and 500 mg/day of i.v. methylprednisolone, 9 all of which are considerably higher than the dose applied in this patient.…”
Section: Discussionmentioning
confidence: 99%